Control of Dental Caries in Children and Adolescents Using Fluoride: An Overview of Community-Level Fluoridation Methods - América Patricia Pontigo-Loyola; Martha Mendoza-Rodriguez; Rubén de la Rosa-Santillana; Maria Gracia Rivera-Pacheco; Horacio Islas-Granillo; Juan Fernando Casanova-Rosado; María de Lourdes Márquez-Corona; José de Jesús Navarrete-Hernández; Carlo Eduardo Medina-Solís; David J. Manton (MDPI AG, 2024)
The maintenance of oral health is a crucial aspect of general well-being; however, a significant proportion of the worldwide population experiences a range of oral diseases. Dental caries is a highly prevalent non-communicable disease globally, especially in children and adolescents. Fluoride is involved in the control of dental caries, primarily by decreasing the critical pH for dental hard tissue dissolution and decreasing enamel solubility. Due to the substantial data supporting the efficacy of fluoride in controlling dental caries, many community-level fluoridation initiatives have been devised and executed as global public health preventive interventions. These initiatives encompass the fluoridation of water, salt, and milk. Water fluoridation is considered safe and effective when fluoride levels are maintained within the recommended range (0.6 to 1.1 mg/L). Salt fluoridation has a cariostatic potential similar to that of water fluoridation, and a fluoride concentration of 250 micrograms per gram in salt is not associated with an increased risk of developing dental fluorosis. However, there is currently an effort to reduce the consumption of table salt in order to mitigate the harmful effects of excessive salt consumption. It has been hypothesized that fluoride food supplementation, such as fluoridated milk, is associated with a decrease in caries experience in permanent teeth; however, the effect is not clear in primary teeth. Public-level fluoride interventions are more cost-effective than the operative care of caries lesions and limit the burden of care. The administration of fluorides should be conducted using safe methods, limiting ingestion, and adhering to the guidelines set by international and national health agencies in each country. This is particularly important when considering children with developing dentitions. Fluoride is an important tool in the control of dental caries, but it is crucial to combine it with good oral hygiene, a healthy diet, and regular visits to a dental professional to maintain long-term oral health.